Effect of dog breed and body conformation on vertical ground reaction forces, impulses, and stance times - Voss, K; Wiestner, T; Galeandro, L; Hässig, M; Montavon, P M (Veterinary and comparative orthopaedics and traumatology, 2011)
To assess whether fully normalised vertical ground reaction forces and stance times obtained at a trot depend on dog breed or body conformations. Peak vertical forces (PVF), vertical impulses (VI), stance times (ST), and ratio of forelimb impulse to total impulse (RVI) of 54 dogs of seven different breeds were normalised to body weight and body size according to the theory of dynamic similarity, and were tested for differences between breeds. Breeds were Borzoi, Bernese Mountain dog, Great Dane, Labrador Retriever, Landseer, Rhodesian Ridgeback, and Rottweiler. Body length ratio (BLR) and body mass index (BMI) were also compared between breeds. Significant differences between breeds were found for the normalised forelimb PVF, VI and ST, and hindlimb PVF. Looking at individual breeds, it was most evident that Borzois had a lower forelimb VI, and a higher hindlimb PVF than the other breeds. This resulted in Borzois having a lower RVI compared to other dogs, indicating a more caudally located centre of gravity. Only a few differences in gait parameters were found between other dog breeds. The BMI was significantly lower in Borzois than in other breeds, but was otherwise not associated with gait parameters. Force plate data of dogs of different breeds are not necessarily comparable, even after full normalisation to body weight and body size. Group comparisons should only be made when the groups consist of breeds with similar body conformations.